2017
DOI: 10.24258/jba.v13i1.275
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Kepemimpinan, Budaya Organisasi, dan Lingkungan Kerja Serta Kepuasan Kerja Terhadap Kinerja Pegawai Wilayah Kecamatan Kota Tarakan

Abstract: The purpose of this study is to determine the significance of the influence of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
1
1
0
6
Order By: Relevance
“…The results of this study are in line with the results of previous studies (Nugrahaningsih & Julaela, 2017;Safitri, 2017;Siagian & Khair, 2018;Sriekaningsih, 2017) which state that Organizational Culture, Performance, Job satisfaction is positive, so it can improve economic performance significantly, and this means that efficiency will increase in achieving a goal.…”
Section: Results and Discussion The Influence Of Organizational Cultu...supporting
confidence: 91%
“…The results of this study are in line with the results of previous studies (Nugrahaningsih & Julaela, 2017;Safitri, 2017;Siagian & Khair, 2018;Sriekaningsih, 2017) which state that Organizational Culture, Performance, Job satisfaction is positive, so it can improve economic performance significantly, and this means that efficiency will increase in achieving a goal.…”
Section: Results and Discussion The Influence Of Organizational Cultu...supporting
confidence: 91%
“…This will have a beneficial effect on the employee, and control is required without the use of official bureaucracy. Maabuat (2016) and Sriekaningsih (2017), on the other side, concluded that organizational culture had no effect on performance. Organizational commitment, in addition to organizational culture, influences employee performance.…”
Section: Introductionmentioning
confidence: 99%
“…Lebih lanjut kinerja selain dipengaruhi oleh budaya namun juga ada faktor lain seperti gaji, gaji menjadi motivasi yang mempengaruhi kinerja karyawan. Kinerja karyawan dapat dipengaruhi oleh buadaya organisasi dan komitmen organisasi, oleh karena itu harus tercipta motivasi dalam diri karyawan serta kepuasan kerjanya Terdapat gap penelitian sebelumnya yang meneliti tentang budaya organisasi tidak berpengaruh terhadap kinerja karyawan seperti (Sriekaningsih, 2017), (Haryanti Shinta, 2015), (Megantara et al ., 2019). Moivasi kerja tidak berpengaruh terhadap kinerja karyawan (Budi et al ., 2019) (Dewi Shanty, 2017), (Hasmalawati, 2018) dan kepuasan kerja tidak berpengaruh terhadap kinerja karyawan (Tarjo, 2019b).…”
Section: A Pendahuluanunclassified